Pengembangan Bahan Ajar Berbasis RADEC untuk Meningkatkan Keterampilan Proses Sains - Farhan Baehaki; Ni'matul Murtafi'ah; Azalia Adelin; Vivo Prahasta (Jurnal Kajian Pendidikan IPA, 2026)
The government has created a standard graduate profile that includes 21st-century competencies for prospective Medical Laboratory Technology (TLM) students. One of the skills the government focuses on is the development of Science Process Skills (SPS). Student-centered learning through various learning models has been implemented to improve SPS. However, the process has not been significantly successful. Students tend to be passive due to their lack of prior knowledge, so they focus on recording and writing rather than being actively involved. Therefore, the RADEC Learning Model (Read, Answer, Discuss, Explain, and Create) can be an alternative in supporting students' prior knowledge because it consists of Pre-Lecture (Read and Answer) and Lecture (Discuss, Explain, and Create) activities. Another obstacle is the breadth of material due to easy internet access, making it difficult for students to find and select valid information. The goal of this project is to create RADEC-based instructional resources that can help TLM students improve their science process abilities. The Development & Validation approach, which consists of three stages, is used in this study: 1) literature review; 2) construction; and 3) improvement. The 4-STMD approach was used in the creation of instructional materials. Thirty students studying Medical Laboratory Technology and seven specialists participated in the evaluation. A readability test sheet and an expert validation sheet were the tools utilised in the data collection procedure. The results showed that the teaching materials had excellent validity (conformity >80%) and good readability (>70%) in facilitating the development of science process skills. Therefore, the developed teaching materials can be implemented in lectures.Keywords: medical laboratory technology, RADEC, science process skills, teaching materials